Facile one-pot electrosynthesis of high photoreactive hexacoordinated Si with Zr and Zn catalyst - Norzahir, Sapawe; Muhammad Farhan, Hanafi (The Royal Society of Chemistry, 2015)
A facile one-pot electrochemical method was used to synthesize highly photoreactive hexacoordinated Si with Zr and Zn catalysts, which gave complete photodecolorization of methylene blue after 1 h of irradiation under visible light.